2020
DOI: 10.1002/pol.20190070
|View full text |Cite
|
Sign up to set email alerts
|

Linear Bio‐Based Water Soluble Aromatic Polymers from Syringic Acid, S Type Degradation Fragment from Lignin

Abstract: Degradation products of lignin, a widely available biopolymer, represent the most abundant feedstock for aromatics in nature. In this work, we focused on syringic acid, derived from lignin S‐type monolignol, to synthesize different monomers for radical polymerization. The resulting polymers have molecular weight spanning over a wide range, which depends on the monomer, with up to Mn = 1,100,000 g.mol−1 and Đ = 3.0. The novel polymers exhibit a thermal stability higher than 350°C and differentiated glass transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…199,200 Degradation of S-unit-rich lignin can result in the production of syringic acid. 201 This compound can also be extracted from lignin using wood-rotting fungi. 202 Recently, researchers have shown marked attention towards this compound and different biobased polymer, such as polyesters, polyamide, high molecular weight water-soluble polymers were produced using syringic acid.…”
Section: Benzoic Acid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…199,200 Degradation of S-unit-rich lignin can result in the production of syringic acid. 201 This compound can also be extracted from lignin using wood-rotting fungi. 202 Recently, researchers have shown marked attention towards this compound and different biobased polymer, such as polyesters, polyamide, high molecular weight water-soluble polymers were produced using syringic acid.…”
Section: Benzoic Acid Derivativesmentioning
confidence: 99%
“…Synthesis of polystyrene-like polymers were also explored using syringic acid by functionalization, protection and radical polymerization. 201 Monomer 143 was produced from syringic acid functionalized with vinyl benzyl chloride in DMF, which shows 90% AE, sEF value 18.5 and 52% yield (Table S1 3,4,5-Trihydroxybenzoic acid, also known as gallic acid, is another benzoic acid derivative that can be derived from lignin. 203 Gallic acid can be found freely available or in the form of esters in tea leaves and also in the mature seeds and roots of Norway spruce.…”
Section: Benzoic Acid Derivativesmentioning
confidence: 99%
“…A sustainable approach to solve this plastic waste problem to some extent is designing and using renewably sourced and biodegradable polymers. [235] Examples are the synthesis of biobased acrylic polymers using 2H-HBO derived from renewable sources [236] or from bio-based Cyrene TM , [237] bio-based watersoluble aromatic polymers produced from lignin-based compounds, [238] bis-phenols, and trisphenol from renewable resources for the production of poly(ester urethane)s, and epoxy-amine resins, [239][240][241][242][243] to name a few. Edible films have also entered the packaging market as a sustainable solution to plastic waste.…”
Section: Other Challengesmentioning
confidence: 99%
“…( Rasmussen et al, 2016 ). Closing, 4-Hydroxybenzaldehyde is described as aldehyde monomer of lignin ( Hu et al, 2018 ) and syringic acid is reported as small phenolic degradation fragments from S and G-type lignins ( Longe et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%